Potential of Health and Demographic Surveillance System in Asthma and Chronic Obstructive Pulmonary Disease Microbiome Research - Agarwal, Dhiraj; Dhotre, Dhiraj; Patil, Rutuja; Shouche, Yogesh; Juvekar, Sanjay; Salvi, Sundeep (Frontiers in Public Health, 2017)
Health and demographic surveillance system (HDSS) is a population-based health and vital event registration system that monitors demographic and health events in a geographically defined population at regular intervals. Human microbiome research in the past decade has been the field of increasingly intense research much due to its demonstrated impact upon various health conditions including human chronic airway diseases such as asthma and chronic obstructive pulmonary disease (COPD). Many confounding factors have been revealed to play a role in shaping the microbiome in chronic airway diseases. Asthma and COPD follows a typical pattern of disease progression, which includes stable and exacerbation state in which the microbiota is known to vary. However, many such studies lack extensive and longitudinal sampling with inadequate metadata, which has resulted in the inconsistencies in the observations. HDSS provides such a platform, which can offer a deeper understanding of the role of the microbiome in human health. In this review, we highlight opportunities and limitations in microbiome research with the help of studies conducted on chronic airway diseases like asthma and COPD. In addition, we also emphasize on the benefits of HDSS and future directions in lung microbiome research.